Anonymous
Anonymous asked in Science & MathematicsAgriculture · 2 months ago

# Help me solve this equation ?

x^2 = (x+3)/2

Relevance
• 2 months ago

x^2 = (x + 3)/2

2x^2 = x + 3

2x^2 - x - 3 = 0

(2x - 3)(x + 1) = 0

x = 3/2 or x = -1

• Lv 4
2 months agoReport

• 2 months ago

2x^2 = x + 3

2x^2 - x - 3 = 0

(2x - 3)(x + 1) = 0

2x - 3 = 0

x = 3/2 = 1.5

&

x + 1 = 0

x = -1

• Lôn
Lv 7
2 months ago

2x^2 = x + 3

2x^2 - x - 3 = 0

2x^2 - 3x + 2x - 3 = 0

x (2x - 3) + 1 (2x - 3 ) = 0

(x + 1)(2x - 3) = 0

Either x + 1 = 0 ..... x = -1

Or 2x - 3 = 0...... x = 3/2

• 2 months ago

Multiplying by 2 we get:

2x² = x + 3

Re-arranging we get:

2x² - x - 3 = 0

Then factorising gives:

(2x - 3)(x + 1) = 0

Hence, x = 3/2 or x = -1

:)>

• Lv 4
2 months agoReport

• 2 months ago

Multiply both sides by 2:

2x² = x + 3

Get everything on one side:

2x² - x - 3 = 0

Factor:

2x² - 3x + 2x - 3 = 0

x(2x - 3) + 1(2x - 3) = 0

(x + 1)(2x - 3) = 0

Set those each to zero:

x + 1 = 0

x = -1

or

2x - 3 = 0

2x = 3

x = 3/2

x = 1½